Titanium Immobilized with an Antimicrobial Peptide Derived from Histatin Accelerates the Differentiation of Osteoblastic Cell Line, MC3T3-E1 - Makihira, Seicho (Molecular Diversity Preservation International (MDPI), 2010)
The objective of this study was to evaluate the effect of titanium immobilized with a cationic antimicrobial peptide (JH8194) derived from histatin on the biofilm formation of Porphyromonas gingivalis and differentiation of osteoblastic cells (MC3T3-E1). The titanium specimens (Ti) were immobilized with JH8194, according to the method previously described. The colonization of P. gingivalis on JH8194-Ti was significantly lower than that on control- and blocking-Ti. JH8194-Ti enhanced the mRNA expressions of Runx2 and OPN, and ALPase activity in the MC3T3-E1, as compared with those of control- and blocking-Ti. These results, taken together, suggested the possibility that JH8194-Ti may be a potential aid to shorten the period of acquiring osseointegration.